In vitro antioxidant potency of some smaller chain glycopeptides with the prediction of IC50 values - Nagarajan, Kandasamy; Grover, Parul; Ghai, Roma; Teharia, Ayushi; Chauhan, Sanjeev; Sahoo, Jagannath (International Journal of Pharmacology and Toxicology, 2016)
Hydrogen peroxide, 1,1-Diphenyl-2-picryl-hydrazyl (DPPH) and Phosphomolybdenum in-vitro assay was employed to determine the antioxidant potency of glycopeptides RN Mannose, RK starch, RNRN Mannose and RHRCR Starch using ascorbic acid as the standard drug. The percentage scavenging activity of the glycopeptides were determined at different concentrations and the IC50 value of the test compounds were subsequently compared with that of ascorbic acid. RN Mannose was found to be most potent antioxidant compound. Also, Swiss dock study was performed with three glycopeptides, viz., RHRCR Mannose, RN Mannose and RNRN Mannose.Among these, RHRCR Mannose was found to have the best affinity for the receptor with stearic energy -0.2306kcal/mol.